A Case of Cardiac Tamponade in a Patient with Metastatic Renal Cell Carcinoma on Pazopanib Treatment - Vinu Sarathy; Sriniivas Belagutty Jayappa; Thianesh Waran; Radheshyam Naik (Case Reports in Oncological Medicine)
Asymptomatic minimal pericardial effusion may be frequently found in patients with hypothyroidism. Cardiac tamponade secondary to hypothyroidism is rarely referenced in medical literature. Hypothyroidism as an adverse effect of pazopanib (tyrosine kinase inhibitor) treatment leading to cardiac tamponade is an even rarer occurrence. Here, we report an unusual case of a 71-year-old male, with a case of renal cell carcinoma on pazopanib treatment presenting with shortness of breath who was found to have hypothyroidism with a large pericardial effusion leading to cardiac tamponade. The patient did not have any prior reports of thyroid-stimulating hormone (TSH) or thyroid hormone levels at presentation. No such case of cardiac tamponade due to hypothyroidism as an adverse effect of pazopanib tablet treatment has been reported to our knowledge.